An improved 2×2 array antenna using both-sided microwave integrated circuit technology for circular polarization - Piyas Chowdhury; Nishako Chakma; Abu Hena Murshed; Md. Azad Hossain; Quazi Delwar Hossain (Institute of Advanced Engineering and Science, 2023)
A circularly polarized microstrip patch array antenna using both-sided microwave integrated circuit (MIC) technology with a triple feed network has been proposed in this article. The antenna elements, feed structure and both-sided MIC technology are used and arranged in such a way to obtain circular polarization alongside high gain without using an external matching circuit. The 50 Ω microstrip line is used to energize the antenna where the antenna’s total feed network is made up of both series and parallel combinations of microstrip and slot line. The antenna was realized using Teflon glass fiber substrate (εr)=2.15 with a thickness of 0.8 mm. The antenna has some splendid parameters including S11 of less than -35 dB, a gain of 12 dBi with an omnidirectional pattern and an axial ratio of 0.7 dB at the operating frequency. The antenna possesses a bandwidth of 430 MHz (4.22%) after operating at X-band in the frequency spectrum. The antenna’s simulated parameters were investigated with the help of advanced design system (ADS) simulation software in microwave momentum mode.